Obstacles to sports professionalism in the legal and financial aspect of some clubs in the Iraqi Premier League in football from the point of view of the administrators - Mohamed Salim; MOHAMMED ALHAYALI (مجلة الرافدين للعلوم الرياضية, 2023)
The study aimed to, Designing a questionnaire about the obstacles to professionalism in the legal and financial aspect of some clubs in the Iraqi Premier League in football from the point of view of the administrators,dentifying the percentages of obstacles to sports professionalism in the legal aspect of some Iraqi Premier League clubs from the point of view of the administratorsIdentifying the ratios of obstacles to sports professionalism in the financial aspect of some Iraqi Premier League clubs from the point of view of the administrators,The descriptive approach was used in the survey method, and the research community included (88) training from some Iraqi Premier League football clubs (20) paragraph, and its apparent validity was confirmed, as well as the stability of the tool, and the researcher used in the statistical treatments the percentage, the arithmetic mean, the Pearson correlation coefficient, the Spearman-Brown equation, the Guttman equation, and Alpha Cronbach through the (spss) program,The researchers concluded that there are obstacles in the legal aspect in greater proportions than they are in the financial aspect, and there are obstacles in the financial aspect in large proportions. Orientation towards the development of professional regulations focusing mainly on the legal aspect.